John Muir, man of the wild places - Greene, Carol (Chicago : Childrens Press, 1991)
A biography of the naturalist who was an early proponent of wilderness preservation and helped start the Sierra Club.
Includes index.
Book Links (A.L.A.)
2.8
K-3
Keywords: Muir, John, -- 1838-1914 -- Juvenile literature; Muir, John, -- 1838-1914.; Naturalists -- United States -- Juvenile literature; Conservationists -- United States -- Juvenile literature; Naturalists; Conservationists; Muir, John -- 1838-1914.; Naturalists -- Biography; Conservationists -- Biography